Insulated Isothermal Reverse Transcriptase PCR (iiRT‐PCR) for Rapid and Sensitive Detection of Classical Swine Fever Virus. Issue 5 (27th January 2015) - Lung, O.; Pasick, J.; Fisher, M.; Buchanan, C.; Erickson, A.; Ambagala, A.
Summary: Classical swine fever (CSF) is an OIE‐listed disease that can have a severe impact on the swine industry. User‐friendly, sensitive, rapid diagnostic tests that utilize low‐cost field‐deployable instruments for CSF diagnosis can be useful for disease surveillance and outbreak monitoring. In this study, we describe validation of a new probe‐based insulated isothermal reverse transcriptase PCR (iiRT‐PCR) assay for rapid detection of classical swine fever virus (CSFV) on a compact, user‐friendly device (POCKIT ™ Nucleic Acid Analyzer) that does not need data interpretation by the user. The assay accurately detected CSFV RNA from a diverse panel of 33 CSFV strains representing all three genotypes plus an additional in vitro ‐transcribed RNA from cloned sequences representing a vaccine strain. No cross‐reactivity was observed with a panel of 18 viruses associated with livestock including eight other pestivirus strains (bovine viral diarrhoea virus type 1 and type 2, border disease virus, HoBi atypical pestivirus), African swine fever virus, swine vesicular disease virus, swine influenza virus, porcine respiratory and reproductive syndrome virus, porcine circovirus 1, porcine circovirus 2, porcine respiratory coronavirus, vesicular exanthema of swine virus, bovine herpes virus type 1 and vesicular stomatitis virus. The iiRT‐PCR assay accurately detected CSFV as early as 2 days post‐inoculation in RNA extracted from serum samples of experimentally infected pigs, before appearance of clinical signs. The limit of detection (LOD95% ) calculated by probit regression analysis was 23 copies per reaction. The assay has a sample to answer turnaround time of less than an hour using extracted RNA or diluted or low volume of neat serum. The user‐friendly, compact device that automatically analyses and displays results could potentially be a useful tool for surveillance and monitoring of CSF in a disease outbreak.